Microfabricated microbial fuel cell arrays reveal electrochemically active microbes. - Huijie Hou (Public Library of Science (PLoS), 2009)
Microbial fuel cells (MFCs) are remarkable "green energy" devices that exploit microbes to generate electricity from organic compounds. MFC devices currently being used and studied do not generate sufficient power to support widespread and cost-effective applications. Hence, research has focused on strategies to enhance the power output of the MFC devices, including exploring more electrochemically active microbes to expand the few already known electricigen families. However, most of the MFC devices are not compatible with high throughput screening for finding microbes with higher electricity generation capabilities. Here, we describe the development of a microfabricated MFC array, a compact and user-friendly platform for the identification and characterization of electrochemically active microbes. The MFC array consists of 24 integrated anode and cathode chambers, which function as 24 independent miniature MFCs and support direct and parallel comparisons of microbial electrochemical activities. The electricity generation profiles of spatially distinct MFC chambers on the array loaded with Shewanella oneidensis MR-1 differed by less than 8%. A screen of environmental microbes using the array identified an isolate that was related to Shewanella putrefaciens IR-1 and Shewanella sp. MR-7, and displayed 2.3-fold higher power output than the S. oneidensis MR-1 reference strain. Therefore, the utility of the MFC array was demonstrated.